Synthesis of furfural from agricultural residues in the Philippines for local furfural production - Guerrero, Rodel D. (2013)
Furfural is produced commercially by the acid hydrolysis of pentosan polysaccharides from nonfood residues of food crops and wood wastes. It is an essential chemical substance utilized in the derivation of other valuable chemical such as furfuryl alcohol which is the basic component for the production of a furan resin thermoset. The main source of pentosans is lignocelluloses that can be found in biomass. Pentosans from coconut shell, coconut husk, pineapple bagasse and water hyacinth, which are available agricultural wastes in the country, were used in this study. Given that the Philippines is an agricultural country, the country has a sustainable source of agricultural residues and could potentially become a producer of furfural. The laboratory synthesis of furfural was done by acid catalyzed hydrolysis. The acid hydrolyses were carried out at 180˚C using dilute (0.2 m) sulfuric acid for different hydrolysis times. Results show that furfural yield increases as digestion time increases, but only up to a certain hydrolysis time, different for every raw material, for which the maximum average percent mass furfural yield can be obtained. After which, a decrease in mass yield will be noticed. The effects of digestion time, operating temperature and acid catalyst concentration with respect to the mass furfural yield from coconut shell were examined using ANOVA and Box-Behnken. Correspondingly, a sample furan resin, furfural-acetone resin, was made utilizing the furfural produced in the laboratory experiment.
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Furfural -- Philippines